PSV703 : Multimedia in visual art education / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2023)
At the end of the course, students should be able to: a. Apply the principles of computer-based multimedia with respect to its use in designing and developing new teaching and learning tools. b. Analyze issues of good practices in the use of commercial multimedia applications in schools, colleges or universities and its impact on teaching and learning. c. Design and develop an interactive multimedia application as a new media for the teaching and learning of visual art. d. Evaluate the applications produced during the module or existing commercial multimedia applications.